Using acidic-modified bentonite for anaerobically digested sludge conditioning and dewatering. (February 2020) - Masihi, Hamidreza; Badalians Gholikandi, Gagik
Abstract: In this study, the acidic-modified bentonite (AMB) was developed to enhance conditioning and dewatering processes of anaerobically digested sludge (ADS) for the first time and its performance was compared with inorganic salts, e.g. FeCl3, AlCl3, Al2 (SO4 )3 and Fe2 (SO4 )3 . AMB structural changes were investigated employing XRD, XRF, FT-IR and specific surface area tests. AMB reduced the specific resistance to filterability (SRF), capillary suction time (CST) and time to filter (TTF) of the sludge by 95.8%, 90.4% and 80.8%, respectively. Moreover, it reduced the sludge compressibility and increased filtration yield significantly. Also, sludge conditioning with the AMB resulted in a significant increase in the sludge particles size and formation of denser and stronger flocs. In order to evaluate the related sludge conditioning mechanism, zeta potential, bound water, extracellular polymeric substances (EPS) and XRF tests were conducted. It was determined that AMB acts as physical and chemical conditioner. Dewatering of conditioned sludge with AMB utilizing a filter press resulted in the sludge with 41% dry solids (DS). In addition, the economic survey showed that the cost of conditioning by using AMB is $ 33.79 USD/t DS. In general, it can be concluded that AMB has an effective performance in conditioning and dewatering of anaerobically digested sludge and is economically affordable in comparison to common polymers. Graphical abstract: Image 1 Highlights: Acidic-modified bentonite (AMB) decreased sludge compressibility by 20%. AMB increased sludge filtration yield by 810%. AMB acts as a physical-chemical conditioner. AMB is an efficient and low-cost inorganic conditioner for sludge handling.